THE EFFECT OF CONSUMER MOTIVATION ON HALAL FOOD PURCHASE DECISIONS ON STREET TRADERS OF KESAWAN MEDAN AREA IN THE PANDEMIC PERIOD OF COVID 19 - Mutia Arda; Yayuk Hayulina Manurung (Proceeding International Seminar of Islamic Studies, 2021)
: One of the impacts during the Covid 19 pandemic was an increase in the number of open unemployment, including in big cities like Medan. At the end of 2020, many Medan City people tried their luck selling food in the Kesawan Medan area. Even though at this time the corona pandemic still existed, some consumers continued to shop at street traders in the Kesawan area of Medan. There are many factors that keep some people shopping at street traders in the Kesawan area of Medan, for example, with their needs that must be met, namely buying food. The motivation of consumers to shop for halal food at street traders is because the prices of halal food are relatively cheap even during the Covid-19 pandemic. This study aims to analyze the effect of consumer motivation on purchasing decisions of halal food at street traders in the Kesawan area of Medan. Primary data were collected through a questionnaire to 100 respondents. The analysis technique used is Simple Linear Regression. Based on the results of the analysis, it is known that consumer motivation has a positive and significant effect on purchasing decisions for halal food at street traders in the Kesawan area of Medan. Keywords: Consumer Motivation, Halal Food, Purchase Decisions